Risk perceptions, misperceptions and sexual behaviours among young heterosexual people with gonorrhoea in Perth, Western Australia - Lobo, Roanna; Rayson, J.; Hallett, Jonathan; Mak, D.B. (2020)
Background: Notification rates of gonorrhoea in Australia for heterosexual young adults rose by 63% between 2012 and 2016. In Western Australian major cities, there was a 612% increase among non-Aboriginal females and a 358% increase in non-Aboriginal males in the ten-year period 2007-2016. A qualitative public health investigation was initiated to inform appropriate action. Methods: Eighteen semi-structured telephone interviews were conducted with non-Aboriginal heterosexual young adults aged 18-34 years living in Perth, Western Australia, who had recently been notified to the Department of Health with gonorrhoea, to explore the context of their sexual interactions and lifestyles which could have predisposed them to contracting gonorrhoea. Data were thematically analysed. Results: Common themes were having several casual sexual partners, limited communication between sexual partners about condom use or sexual history prior to engaging in sexual activity, inconsistent condom use, normalisation of some sexually transmissible infections amongst young people, and poor understandings and assessment of sexually transmissible infection risk. Conclusion: The findings support public health interventions that focus on communication between sexual partners and shifting of risk perceptions in sexual health education programs, ensuring accessibility of quality sexual health information, increasing condom accessibility and acceptability, and on strategies for addressing misperceptions of young people in relation to sexually transmitted infections.